Toward a Poetics of the Anglophone Arab Campus Novel - Benaziza, Selma; Awad, Yousef (Dirasat: Human and Social Sciences, 2023)
This paper aspires to delineate the poetics of the Anglophone Arab Campus novel. It shows how the genre of the campus novel, which has always been perceived as exclusively American and European, has now reached the Arab region and it took a local shape. This research proves that the Arab world, via the works of Arab writers in the diaspora, is witnessing the birth of the genre of the campus novel. It highlights some of the basic features of the western campus novel and how the selected novels appropriate these features. This paper deals with Laila Lalami’s Secret Son (2009), Leila Aboulela’s The Kindness of Enemies (2015), and Isabella Hammad’s The Parisian (2019). These novels are selected because they highlight different campuses, and therefore, they represent different experiences of Arab academics and students. Some of the aspects that will be discussed throughout the research are the microcosmic relationship between the campus and real life, the state of xenophobia that Arab academics and students face in the west, the process of the protagonists’ growth in the university as well as satire and love affairs.